EFIKASI IBADAH DARING MENJAWAB TANTANGAN DAN PELUANG DALAM ERA DIGITAL - Pasaribu, Linda Marlina (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2025)
The COVID-19 pandemic has encouraged churches to utilise digital technology in the conduct of worship, resulting in a new format of ‘new worship’ that takes place online. The pandemic has passed, but online worship in reality is still maintained by some churches. This research explores the challenges and opportunities of online worship in providing an effective spiritual experience. With a focus on the role of symbolism, digital media and congregational participation, this study found that the efficacy of online worship does not depend on physical space, but how new media creates encounters between people and God. This research asserts that new worship can be an authentic sacred space in the digital era. This research was conducted using a qualitative method by conducting a literature review on the sacredness of ‘new worship’. The results showed that both online and onsite the sacredness of worship is not diminished if practised properly. So that whether online, people can feel an encounter with God.